Clinical characteristics and risk factors for mortality in adult patients with persistent candidemia. Issue 3 (September 2017) - Kang, Seung Ji; Kim, Seong Eun; Kim, Uh Jin; Jang, Hee-Chang; Park, Kyung-Hwa; Shin, Jong Hee; Jung, Sook In
Summary: Background: We investigated the clinical characteristics and risk factors for mortality in adults with persistent candidemia. Methods: All patients ≥18 years old with candidemia in two Korean tertiary hospitals from 2007 to 2014 were investigated. Persistent candidemia was defined as isolation of the same Candida species ≥5 days after initiation of antifungal therapy. Non-persistent candidemia was defined as candidemia persisting for ≤3 days after initiation of antifungal therapy. Results: Candida tropicalis (29.2%) was the most common pathogen in persistent candidemia, and Candida albicans (35.9%) was the most common in non-persistent candidemia. Central venous catheter (CVC) (OR, 1.99; 95% CI, 1.05–3.78; P  = 0.034), longer hospital stay (OR 1.01; 95% CI, 1.01–1.02; P  = 0.025), and severe sepsis (OR 2.25; 95% CI, 1.11–4.56; P  = 0.024) were independent risk factors for persistent candidemia. C . tropicalis was independently related to 30-day mortality (OR, 4.12; 95% CI, 1.27–13.36; P  = 0.018), together with septic shock (OR, 5.81; 95% CI, 1.32–24.70; P  = 0.017) and use of a corticosteroids (OR, 5.31; 95% CI, 1.07–26.29; P  = 0.041) in persistent candidemia. Conclusion: C . tropicalis is the predominant pathogen and cause of death in patients with persistent candidemia. Highlights: Candida tropicalis was the most common pathogen in adult with persistent candidemia. CVC and severe sepsis were independently associated with persistent candidemia. C. tropicalis was a risk factor for mortality in persistent candidemia.